3,5-Disubstituted 2-Aminopyridines via Nickel-Catalyzed Cycloaddition of Terminal Alkynes and Cyanamides - Zhong, Yao; Spahn, Nathan A.; Stolley, Ryan M.; Nguyen, Minh H.; Louie, Janis (Synlett, 2015)
The regioselectivity of the Ni/SIPr-catalyzed cycloaddition of terminal alkynes and cyanamides was explored. In general, 3,5-disubstituted 2-aminopyridines were formed as the major product.
Keywords: nickel; catalyst; cycloaddition; 2-aminopyridines; regioselectivity